Juridical Analysis of the Distribution of Joint Assets in Divorce According to Indonesian Positive Law - Carissa Patricia Hong; Jelita Safitri Ananda; Muh. Abriel Givari Riser (IJRAEL: International Journal of Religion Education and Law, 2023)
In a divorce, there is a process of dividing joint assets. Issues regarding joint assets often occur between ex-husbands and ex-wives. For Muslims, the provision for sharing joint assets is contained in article 97 of the Compilation of Islamic Law (KHI) that "widows or widowers who are divorced, each is entitled to half of the joint assets as long as the marriage agreement is not specified otherwise". Referring to this article, it means that a husband and wife who are divorced are entitled to half or half of the joint property as long as there is no marriage agreement. Meanwhile, for adherents of other religions it is regulated in the Criminal Code which is stated in Article 128 of the Civil Code. According to the Civil Code, division can be made based on the distribution of evidence submitted by plaintiffs and defendants. Basically, these two articles stipulate that in the event of a divorce, the property is divided 50:50. The division of joint assets can be filed together with a divorce suit and does not have to wait for a divorce decision from the court. The formulation of the problem in this study is a juridical analysis of the division of joint assets in divorce according to Indonesian positive law. This research uses normative research with descriptive research specifications and uses primary legal materials, secondary legal materials and tertiary legal materials which are arranged systematically, reviewed, and then concluded.